The Influence of Compensation and Workload on Employee Satisfaction at PT Inti Logam Sukses Abadi - Alfiani Cita Maulinda; Teguh Kurniyanto (Escalate : Economics and Business Journal, 2026)
Job satisfaction is a crucial factor in determining employee productivity, loyalty, and performance. At PT Inti Logam Sukses Abadi, issues related to compensation that does not fully comply with minimum wage regulations and uneven workload distribution are still found, which are suspected to affect employee job satisfaction. This study aims to analyze the influence of compensation and workload on employee job satisfaction. The study used a quantitative approach with an associative method. The study population consisted of 78 employees, all of whom were sampled using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and then analyzed using validity and reliability tests, classical assumption tests, simple and multiple linear regressions, correlation coefficients, coefficients of determination, and t-tests and F-tests using SPSS. The results showed that compensation had a positive and significant effect on job satisfaction, while workload had a negative and significant effect on job satisfaction. Simultaneously, both variables significantly influenced job satisfaction, with a coefficient of determination of 35.7%. The study concluded that increasing fair compensation and managing proportional workload are important strategies for improving employee job satisfaction